GC-MS/MS Analysis and Wound Repair Potential of Urtica dioica Essential Oil: In silico Modeling and In vivo Study in Rats - Ben Chira, Ahlem; Kadmi, Yassine; Badraoui, Riadh; Aouadi, Kaïss; Alhawday, Fahad; Boudaya, Mariem; Jamoussi, Kamel; Kallel, Choumous; El Feki, Abdelfattah; Kadri, Adel; Saoudi, Mongi (Current Pharmaceutical Biotechnology, 2025)
BackgroundThe study aimed to assess the antioxidant and wound healing properties of Urtica dioica essential oil (UDEO) through a comprehensive evaluation involving in silico, in vitro, and in vivo analyses. The phytochemistry of UDEO was also investigated to identify trace compounds crucial.MethodsVarious injection methods of the multimode inlet (MMI) in chromatography were investigated to attain lower instrumental detection limits. Subsequently, in silico studies were employed to delve deeper into the potential biological activities of the identified compounds. Standard antioxidative tests, encompassing ABTS•+ and TAC, were performed. In vivo tests centered on wound healing were implemented using rat models. The rats were randomly allocated to four groups: saline solution, vaseline vehicle, cytol centella, and 5% UDEO ointment. Wound healing progress was evaluated through a chromatic study.ResultsGas chromatography combined with triple quadrupole mass spectrometry (GC-MS/MS) analysis revealed the presence of 97 thermolabile compounds in UDEO. Subsequent in silico studies unveiled the potential of identified compounds to inhibit COX-2, TNF-α, and IL-6, suggesting a possible enhancement of anti-inflammatory responses and healing processes. In vitro tests elucidated the notable antioxidant capacity of UDEO, a finding reinforced by wound healing data, revealing a substantial closure rate of 89% following the topical application of UDEO. Notably, fibrinogen and C-reactive protein (CRP) levels were significantly reduced, indicating minimized oxidative stress damage compared to control. Additionally, UDEO exhibited an increase in antioxidant enzyme activities compared to control.ConclusionThe study concludes that UDEO possesses significant antioxidant and wound-healing properties, supported by its rich phytochemical composition. The findings suggest its potential application in therapeutic interventions for oxidative stress and inflammatory conditions.
Keywords: excision wound